Annotated bibliography about Leonese wrestling (1977-2015) - Robles-Tascón, José Antonio; García-Robles, Héctor (Revista de Artes Marciales Asiáticas, 2017)
The purpose of this study was to create an annotated bibliography about Leonese wrestling. The first author's library was the starting point and then the catalogs of the National Library of Spain, Public Libraries of Spain, Spanish University Libraries Network, as well as the Spanish ISBN Agency Database of books published in Spain were consulted by using the keywords “lucha leonesa” and “aluche”. The annotated bibliography comprises a total of 19 monographs, published between 1977 and 2015. As a whole, they show the eminently local dimension of this traditional sport, the support it has received from several public and private institutions, as well as its double dimension as a sport and as a tradition solidly rooted in Leonese culture.